Analisis Potensi Pendapatan Asli Daerah (PAD) Melalui Pajak Bumi dan Bangunan Berdasarkan Kawasan di Kabupaten Barito Kuala - Ahmad Rizali; Muhammad Saleh (PPJP Universitas Lambung Mangkurat, 2021)
This study was conducted to (1) Analyze the potential of PBB-P2 and (2) factors that are obstacles in the PBB-P2 based in the Barito Kuala area. This research sample uses (1) Sampling Area with the lowest PBB-P2 realization in Bakumpai and Kuripan Districts and the highest PBB-P2 realization, namely Alalak and Marabahan Districts, (2) Using purposive sampling with the informant is the Head of the Regional Tax and Retribution Management Agency Barito Kuala Regency and Section Chief. Data analysis uses a calculation of the percentage comparison of potential and realization of PBB-P2. This study proves that the greatest potential of PBB-P2 is located in Alalak District and Marabahan District, while the lowest potential is in Bakumpai and Kuripan Districts. The inhibiting factors are (1) the limitations and capabilities of human resources; (2) : social, economic conditions of the community; and (3): number of taxpayers and living conditions